Design and assessment of in silico screened diosmin incorporated ultra-flexible topical lipid gel system for the treatment of varicose vein - Akhilesh Dubey, Amitha Shetty, Chaithra R. Shetty, Namdev Dhas, Anup Naha, Pratika Bhandary, Srinivas Hebbar (Journal of Applied Pharmaceutical Science, 2024)
The ultra-flexible lipid gel system (UFLGS) consists of bilayer lipid membranes, responsible for highly elastic and deformable vesicles compared to conventional topical systems. Varicose veins are abnormal, dilated blood vessels resulting from weakening in the wall of the blood vessels. A flavonoid diosmin is highly potential to alleviate circulatory issues by altering blood veins’ elasticity and suppleness. Schrodinger 2023-1 suite device was used for molecular docking study. Ultra-flexible lipid nanosuspension (UFLNS) was developed and optimized. Then, they are characterized for Fourier transform infrared spectroscopy, differential scanning calorimetry, entrapment efficiency, transmission electron microscopy, atomic force microscopy, and turbidity measurement studies. After incorporating into the aqueous gelling agent Carbopol 934, Diosmin UFLGS (DUFLGS) was compared with the diosmin conventional gel system (DCGS) for its physicochemical properties. The docking score was –8.507, representing good interaction and binding affinity for nuclear factor-kappaB-inducing kinase. The particle size, polydispersity index, and surface charge of optimized diosmin-loaded UFLNS (DUFLNS) were found to be ideal values 144.56 ± 5.1 nm, 0.397 ± 0.13, and –24 ± 0.9 mV, respectively. The results of DUFLNS, DUFLGS, and DCGS showed skin retention values of 55.5% ± 13%, 83.44% ± 12%, and 66.39% ± 14%, respectively. The sustained release of the DUFLGS is owing to the elasticity of the ultra-flexible lipids, thereby the penetration enhanced compared to DCGS.
Keywords: Diosmin, ultra-flexible lipid nano gel, carbopol, varicose veins